DEFINITIVE MANAGEMENT OF MORBIDLY ADHERENT PLACENTA: ANALYSIS OF MATERNAL OUTCOMES: Morbidly Adherent Placenta - Tahir, Naila; Adil, Muhammad; Afzal, Bushra; Kiani, Sidra; Kiani, Raza; Khan, Shahbaz (Pakistan Armed Forces Medical Journal, 2018)
Objective: To identify risk factors predisposing to morbidly adherent placenta and to study obstetric outcome in such patients. Study Design: Retrospective descriptive study. Place and Duration of Study: Department of Obstetrics and Gynaecology Military Hospital Rawalpindi, from Jan 2014 to Dec 2014. Material and Methods: A total of 54 patients with morbidly adherent placenta were studied retrospectively. Patient’s data including demographic data, previous obstetric history and outcome was collected from hospital records. Data was analyzed by using SPSS version 20. Results: The incidence of morbidly adherent placenta was 4.74 per 1000 deliveries. Mean age of patients was 33.33 ± 2.82 years with mean gestational age of 35.13 ± 0.91 weeks. All patients had history of prior caesarean section with 4 (7.40%) patients having four, 32 (59.25%) having three, 16 (29.62%) having two and 2 (3.70%) having one previous caesarean section. Associated placenta previa was present in 43 (79.62%) patients. Out of 54 patients 39 (72.22%) had placenta accreta, 11 (20.37%) had placenta percreta while 4 (7.4%) had placenta increta. Obstetric hysterectomy was done in 51 patients while in remaining 3 uterus was preserved. Out of these three, one died as a result of septicemia while methotrexate was started in remaining two cases. However an interval hysterectomy was performed in these two cases because of massive postpartum hemorrhage. Conclusion: Previous caesarean section and placenta previa are major risk factors for morbidly adherent placenta. Patient education, antenatal diagnosis with well planned surgical intervention and anticipation of blood loss are keys to successful management.